An aim for men. (2nd July 2016) - Rowan, John
Abstract : It is getting harder and harder to know what a man is supposed to be like, but Aaron Kipnis made a great contribution with his notion of the 'initiated man' who has dared to go in for personal therapy. I want to expand on this idea, and to give some examples of how it works in practice.